Training on Making Educational Game Tools as Learning Resources - Yusnita, Novi Cynthia; Dara Aisyah (Outline Journal of Community Development, 2025)
Early childhood education presents the concept of playing while learning, therefore play activities are part of the learning process. However, in reality teachers do not use a variety of learning resources, so children quickly become bored in the learning process. One learning resource that is appropriate for teachers to use and is in accordance with the concept of playing while learning for early childhood is educational games. The aim of this community service activity is to provide training to teachers in making educational game tools so that these teachers become more creative. The method used in this community service is in the form of training in making educational game tools. After carrying out community service activities by conducting training in making educational game tools for teachers, the results of the evaluation of these activities were that teachers became more creative in designing devices or media used for learning in early childhood.